2013
DOI: 10.4236/ajps.2013.44106
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Anatomical Variations in Rheophytic Ecotype of Violet, Viola mandshurica var. <i>ikedaeana</i> (Violaceae)

Abstract: We compared the leaf morphology and anatomy of the putative rheophytic ecotype of Viola mandshurica W. Becker var. ikedaeana (W. Becker ex Taken.) F. Maek. and its closely related variety, V. mandshurica var. mandshurica. We showed that the leaf of the rheophytic ecotype of V. mandshurica var. ikedaeana was narrower than that of V. mandshurica var. mandshurica. Moreover, the leaf thickness and guard cell size of the rheophytic ecotype of V. mandshurica var. ikedaeana were significantly larger than those of V. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Our results indicated that the stomatal density of riverside populations was significantly higher than that of the inland populations (Table 5). The increase in stomatal density was not, however, a specific differentiation, and some similar cases have been reported in rheophytic adaptation of various angiosperms (Nomura et al, 2006;Ueda et al, 2012;Matsui et al, 2013). Some studies have indicated that changes in stomatal density in response to soil moisture appears to correspond to environmental conditions (Bakker, 1991;Miyazawa, Livingston, & Turpin, 2006;Xu & Zhou, 2008;Sun, Yan, Cui, & Liu, 2014), and several approaches to improve water-use efficiency through the modification of stomatal traits have been tested in model plants (Büssis, von Groll, Fisahn, & Altmann, 2006;Liu, Ohashi-Ito, & Bergmann, 2009;Dow, Berry, & Bergmann, 2014;Dittberner et al, 2018).…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…Our results indicated that the stomatal density of riverside populations was significantly higher than that of the inland populations (Table 5). The increase in stomatal density was not, however, a specific differentiation, and some similar cases have been reported in rheophytic adaptation of various angiosperms (Nomura et al, 2006;Ueda et al, 2012;Matsui et al, 2013). Some studies have indicated that changes in stomatal density in response to soil moisture appears to correspond to environmental conditions (Bakker, 1991;Miyazawa, Livingston, & Turpin, 2006;Xu & Zhou, 2008;Sun, Yan, Cui, & Liu, 2014), and several approaches to improve water-use efficiency through the modification of stomatal traits have been tested in model plants (Büssis, von Groll, Fisahn, & Altmann, 2006;Liu, Ohashi-Ito, & Bergmann, 2009;Dow, Berry, & Bergmann, 2014;Dittberner et al, 2018).…”
Section: Discussionsupporting
confidence: 52%
“…ikedaeana, and Farfugium japonicum var. luchuence had thicker leaves than those of closely related dryland species of R. macrosepalum, V. mandshurica, and F. japonicum, respectively (Nomura, Setoguchi, & Takaso, 2006;Ueda et al 2012;Matsui et al 2013). Therefore, the thick leaves induced along rivers were the general tendency in rheophyte plants because this modification was common to different plant lineages.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations